Establishment of Total Quality Management in the Iranian Seaports - Jafari, Hassan (Journal of Asian Business Strategy, 2013)
This study aimed to determine the readiness level of the studied seaport’ managers for Establishment of Total Quality management (hereinafter referred to as TQM). Thus because all of the ports are of trading kind so they are considered as a servicing organization and due to optimizing the research, the TQM principles such as commitment, customers focus, pragmatism, employee involvement, training and continuous improvement as efficient tools for probing the readiness level of the studied seaport’ managers for Establishment of Total Quality management. Then, for collecting the necessary data, the multiple item questionaries’ is prepared. All the question items are organized according to the above mentioned principles. The main hypothesis that outlined the readiness of the Studied seaport’ managers for Establishment of TQM is on the appropriate level probed and studied here, but finally the result on which revealed by T-test, showed that the studied port is not in an appropriate level for Establishment of TQM. Therefore the main hypothesis of the study is rejected and the secondary hypotheses of the study are rejected, too.